2^nd^ Swiss Vasopressin Consensus: Vasopressin in Septic Shock and other Vasodilatory States - Karim Bendjelid; Tiziano Cassina; Luca Cioccari; Gabor Erdoes; Raymond Friolet; Lucas Liaudet; Peter Steiger; Martin Siegemund (healthbook TIMES Das Schweizer Ärztejournal Journal Des Médecins Suisses)
Vasopressin is a non-catecholaminergic vasopressor with proven advantages in the treatment of vasodilatory states such as septic shock. Its clinical utility in this context is supported by its ability to stabilize blood pressure and tissue perfusion, reduce the norepinephrine dose and mitigate adrenergic side effects.